LAW ENFORCEMENT PRACTICE OF ANTI-CORRUPTION MEASURES IN PUBLIC PROCUREMENT OF GENERAL EDUCATION SCHOOLS (A CASE STUDY OF KYZYLORDA REGION) (Journal of actual problems of jurisprudence, 2025)
The article examines the law enforcement practice of combating corruption in public procurement processes in general education schools of the Kyzylorda region. The main problems are identified, and possible ways to solve them are proposed.The research aims to understand how anti-corruption measures are implemented in practice within the procurement system, what challenges arise, and what steps can make the process more transparent and fair.The scientific value of the study lies in systematizing experience and analyzing the specifics of applying anti-corruption norms in the education sector, thereby expanding the understanding of legal mechanisms for preventing corruption. The practical significance is reflected in the development of recommendations aimed at improving the openness and efficiency of procurement procedures in regional schools.The study employs methods of analysis, comparison, and a systematic approach, as well as the examination of legislation and specific cases of law enforcement practice.The results show that issues of insufficient transparency and control still persist in the procurement process. Therefore, specific measures are proposed to enhance openness, accountability, and the introduction of digital tools.The value of the research lies in revealing the real state of anti-corruption processes in school procurement and offering practical recommendations for their improvement. The findings can be useful for educational institutions and supervisory bodies in strengthening the legality and effectiveness of procurement procedures.Keywords: public procurement, anti-corruption policy, law enforcement, secondary education, Kyzylorda Region.